What hinders team innovation performance? Three-way interaction of destructive leadership, intra-team conflict, and organizational diversity - Choi, Suk Bong; Jung, Ki Baek; Kang, Seung-Wan (Frontiers in Psychology, 2022)
This paper aims to clarify the impact of destructive leadership on team innovation performance. It also explores the relevant conditions that maximize the above relationship. Specifically we examine how intra-team conflict organizational diversity moderate the relationship between destructive leadership team innovation performance. Finally the three-way interaction between destructive leadership intra-team conflict organizational diversity is analyzed for the worst conditions to maximize the negative effect of destructive leadership on team innovation performance. This paper used a cross-sectional design with questionnaires administered to 87 teams with 479 team members working in Korean manufacturing service firms. It applied a hierarchical regression analysis to test the hypothesized relationships including three-way interaction effect among destructive leadership intra-team conflict organizational diversity on team innovation performance. This paper provided empirical insights about how destructive behaviors of team leader hindered team innovation performance. The three-way interaction effects also revealed that the higher the levels of both intra-team conflict organizational diversity the greater the negative effect of destructive leadership on team innovation performance. This paper demonstrates how team leaders’ behavior team organizational conditions result in discouraging overall innovation outcomes. This paper contributes to the innovation leadership literatures by identifying possible leadership type hindering innovation performance at team level the specific conditions their dynamic interaction strengthening the negative effect of destructive leadership on team innovation performance.